1999
DOI: 10.1038/sj.cgt.7700071
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a replication-competent adenovirus (ONYX-015) following intratumoral injection: Intratumoral spread and distribution effects

Abstract: ONYX-015 is an E1B-deleted adenovirus that replicates in and causes lysis of p53-deficient cancer cells selectively. To study the efficiency of intratumoral (i.t.) spread by ONYX-015, we infected specific fractions of tumor cells (two p53-deficient tumor lines and one p53 functional line) in vitro before subcutaneous inoculation into nude mice. Infection of as few as 5% of p53 Ϫ tumor cells prevented tumor development in all cases; infection of 1% of p53 Ϫ tumor cells resulted in significant growth inhibition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(63 citation statements)
references
References 14 publications
1
60
0
2
Order By: Relevance
“…In addition, mixing experiments were performed in which only a fraction of subcutaneously injected cells has been pre-incubated with ONYX-015. As few as 5% of the injected cells needed to be infected to completely abolish tumour growth of cells with mutant p53, whereas no effect on tumour formation by cells with wild-type p53 cells was unchanged (Heise et al, 1999a). These data correlate well with in vitro studies and demonstrated significant therapeutic efficacy of ONYX-015 in vivo with evidence for p53-dependent virus replication.…”
Section: Onyx-015: Mechanisms and Clinical Potential S Ries And Wm Kornsupporting
confidence: 68%
See 1 more Smart Citation
“…In addition, mixing experiments were performed in which only a fraction of subcutaneously injected cells has been pre-incubated with ONYX-015. As few as 5% of the injected cells needed to be infected to completely abolish tumour growth of cells with mutant p53, whereas no effect on tumour formation by cells with wild-type p53 cells was unchanged (Heise et al, 1999a). These data correlate well with in vitro studies and demonstrated significant therapeutic efficacy of ONYX-015 in vivo with evidence for p53-dependent virus replication.…”
Section: Onyx-015: Mechanisms and Clinical Potential S Ries And Wm Kornsupporting
confidence: 68%
“…Although these cells harbour wild-type p53, the pathway is partly inactivated because of a mutation of the p14ARF tumour suppressor gene. Different dosing schedules were tested and showed that virus application for five consecutive days was superior to a one-time application of the same total virus dose (Heise et al, 1999a). Furthermore, of particular importance for the subsequent clinical development of ONYX-015, it was noted that efficacy against this tumour was significantly enhanced when the virus was combined with the chemotherapeutic agents 5-FU or cisplatin (Heise et al, 1997).…”
Section: Onyx-015: Mechanisms and Clinical Potential S Ries And Wm Kornmentioning
confidence: 99%
“…In this regard, a CRAd may achieve better intratumoral spread and penetration due to its replication ability. 32 For clinical application, prevention of hepatic toxicity is also an important consideration. Tumor cells infected with replication-competent Ad may release new viruses in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…First, although viruses rapidly spread in cell culture monolayers, viral spread within a solid tumor mass can be limiting. 17,18 In fact, mathematical modeling of the ''race'' between viral oncolysis and spread versus tumor cell proliferation and outgrowth demonstrates that the infection of the tumor must be diffuse throughout the tumor in order to control it; injection of the tumor ''core'' or periphery only results in tumor ''escape''. 19 The relative inefficiency of viral spread may relate to their relatively large sizes (e.g., 90 nm for adenovirus ), dwarfing antitumoral chemicals, peptides, and even antibodies.…”
Section: Potential Hurdles To Be Overcomementioning
confidence: 99%